CHALLENGES IN PREVENTIVE EXAMINATION AND GYNECOLOGICAL FOLLOW-UP OF RURAL WORKERS IN BRAZIL: AN INTEGRATIVE LITERATURE REVIEW - Vinicius da Silva Pereira, Marcus; Soares da Costa, Douglas; Nayara Coelho Muniz Cardoso, Monique; Saraiva Sales, Eider; Saraiva Sales, Jandir; Mikaelly Santos da Silva, Mara; Barros do Lago, Layanne; Saraiva Sales, Glauber; Milton de Lima Junior, José; Cristinni da Silva Araújo, Emanuelly (Health and Society, 2023)
This article presents an integrative review of the main challenges in the treatment of gynecological diseases among rural female workers in Brazil. Through the analysis of 11 articles published in the last 9 years, we identified that rural female workers face significant barriers in accessing preventive screening and gynecological healthcare. The main obstacles include a lack of adequate access to healthcare services, a scarcity of trained healthcare professionals in rural areas, a lack of awareness about the importance of gynecological health, and gender-based violence. These challenges are compounded by the remote location of rural areas, the lack of suitable healthcare facilities in these regions, and limited transportation availability. To improve access to and the quality of gynecological healthcare for rural female workers, it is necessary to invest in healthcare infrastructure, strengthen the training of healthcare professionals, promote targeted educational programs, and implement public policies that address gender-based violence.